Analisi Pola Spasial Perkembangan Industri Kecil Menengah Dan Industri Rumah Tangga Di Kabupaten Mojokerto - Winne Ayunda Gaiska; Naufal Gama Affandyar; Muhammad Yasin (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
This study aims to find out how the distribution of spatial patterns of the development of small and medium industries and household industries in Mojokerto Regency. The research method used is the Data Collection Method with the Annual Large and Medium Industry Survey (IBS) carried out in full for all industrial companies classified as large and medium which are recorded in the BPS Industry Directory (complete enumeration) and several industry surveys conducted by researchers by conducting a sample and obtained the results that making small and medium industries and home industries a strategy for industrial development in triggering economic growth in Mojokerto Regency.